Tracheobronchomalacia and Excessive Dynamic Airway Collapse: Medical and Surgical Treatment - Kheir, Fayez; Majid, Adnan (Seminars in Respiratory and Critical Care Medicine, 2018)
Excessive central airway collapse (ECAC) is characterized by excessive narrowing of the airway lumen during exhalation leading to dyspnea, cough, mucostasis, recurrent respiratory infections, and poor quality of life. Tracheobronchomalacia and excessive dynamic airway collapse are heterogeneous entities of ECAC and are characterized by a diverse nonspecific symptom profile. Although the pathophysiology of airway mechanics as well as morphology in both entities is different, current evidence so far shows no practical benefit in making such distinction since both have similar symptoms and the diagnostic and therapeutic work-ups are the same. The diagnosis of ECAC should be based on dynamic flexible bronchoscopy and/or dynamic computed tomography scan as well as clinical symptoms that are not fully explained by other lung diseases. Initial treatment of symptomatic ECAC includes treatment of coexisting conditions (such as chronic obstructive pulmonary disease, asthma, gastroesophageal reflux disease, and vocal cord dysfunction) and supportive treatment of dynamic central airway collapse (antibiotics for respiratory infections, aggressive therapy, pulmonary physiotherapy, pulmonary rehabilitation, and continuous positive airway pressure). A short-term stent trial in selected patients with severe symptomatic ECAC is needed to assess whether patients will have improvement in symptoms and thus identify patients who will benefit from surgical central airway stabilization. A multidisciplinary airway team in highly specialized centers with experience in the evaluation and treatment of this patient population is essential for optimal outcomes.
Keywords: excessive central airway collapse; tracheobronchomalacia; excessive dynamic airway collapse